The Influence of Motivation and Herd Mentality on Employee Performance at PT. Safa Mitra Mandiri - Yansah, Beli; Ismuni, Mutdi; Army, Widya Lelisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The world is developing rapidly, including changes that bring both positive and negative impacts to Indonesia. Individual performance within an organization is a crucial element that determines the overall success and achievement of organizational goals. In the context of human resource management, performance is not solely influenced by technical competence and ability, but also by various psychological and social factors that affect individual behavior in the workplace, including Herd Mentality and work motivation.This study aims to determine the extent of the influence of motivation and Herd Mentality on employee performance at PT Safa Mitra Mandiri. This research employs a descriptive quantitative method, utilizing questionnaires to process data through validity and reliability tests. The sampling technique used is non-probability sampling (saturated sampling). The sample consists of 50 employees of PT Safa Mitra Mandiri. The study is intended to provide an overview of how motivation and Herd Mentality influence employee productivity at the company. Quantitative data analysis was conducted using SPSS version 21 to examine the specific population or sample.The results indicate that work motivation has a significant effect on employee performance at PT Safa Mitra Mandiri. Specifically, work motivation has a positive and significant impact on employee performance, with t-count = 4.436 > t-table = 4.346 (Sig = 0.000 < 0.05). This demonstrates that motivation can significantly improve performance and the achievement of company targets. Based on the data analysis, the Herd Mentality variable also significantly affects employee performance at PT Safa Mitra Mandiri. Herd Mentality is an influential factor, and employee performance at the company is categorized as good, meaning Herd Mentality has a positive and significant effect on employee performance with beta = 0.423 and Sig = 0.021 < 0.05. Based on the statistical tests performed, there is a positive and significant influence of both Work Motivation and Herd Mentality on employee performance.